Reduplication in the Nominalization of Children’s Games in Ayacucho Quechua - Torres Castillo, Fernando Aarón (2020)
Reduplication process is a linguistic phenomenon that is present in many languages and has different semantic functions. Sometimes, reduplication is used to express the plurality in a language, meanwhile in others its function is to deverbalize a verb. In this study, we describe the reduplication given in a nominalization process in Ayacucho Quechua for children games. These names are imposed by children and have different recursive constructions due to semantic functions.